Thymus: A Unique Endocrine Gland - Mitra, Anuja; Seth, Dikpravath Kumar; Ghosh, Subho (Indian Science Cruiser, 2016)
The present article encompasses the endocrinological significance of the lymphoid epithelial gland Thymus. Chemical characteristics and physiological role of the thymus hormones are described in detail. Case studies involving biomedical implications of this gland are also discussed.